2015
DOI: 10.18632/oncoscience.275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new miRNA biomarkers associated with HER2-positive breast cancers

Abstract: Human epidermal growth factor receptor 2 (HER2) is overexpressed/amplified in ∼30% breast cancers which are associated with poor prognosis. microRNAs are small non-coding RNA which play an important role in many physiological conditions including cancer. Here we screened and identified many miRNAs which are dysregulated by HER2 overexpression. In line with our quantitative PCR analysis data, in silico analysis of microRNA expression profiles of 1302 breast tumors revealed that miR-146a-5p is up-regulated and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Two miRNAs identified in our cohort-miR-30d and mir-195-5p-inhibit the cell cycle by targeting cyclin E [28,29]. Consistently, their lower expression was noted in biologically aggressive types of breast cancer, i.e., HER2-enriched and basal-like carcinomas [30]. As expected, G1/S transition of mitotic cycle and regulation of cell cycle were identified in the top 20 GO BP categories predicted as miRNA targets in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Two miRNAs identified in our cohort-miR-30d and mir-195-5p-inhibit the cell cycle by targeting cyclin E [28,29]. Consistently, their lower expression was noted in biologically aggressive types of breast cancer, i.e., HER2-enriched and basal-like carcinomas [30]. As expected, G1/S transition of mitotic cycle and regulation of cell cycle were identified in the top 20 GO BP categories predicted as miRNA targets in our study.…”
Section: Discussionsupporting
confidence: 87%
“…E.g. while members of the mir-181 family are up regulated in breast cancer in general, miR-181c in particular is activated by the expression of HER2 gene [25]. Also, miR-140 has been found suppressed by estrogen stimulation in ERα-positive breast cancer cells, most likely due to ER response elements in the flanking element of the miR-140 promoter [26].…”
Section: Introductionmentioning
confidence: 99%
“…A study investigating miR-195 as a biomarker in CRC demonstrated that the downregulation of miR-195 was associated with poor prognosis and lymph node metastasis (6). miR-195 has also been described as a biomarker in cervical cancer, osteosarcoma, adrenocortical cancer and breast cancer (21,(36)(37)(38)(39)(40). Zhao et al (38) found that miR-195 has a higher sensitivity for breast cancer detection, and the expression level of miR-195 has been found to significantly predict the survival rates of patients with HER2-positive breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…miR-195 has also been described as a biomarker in cervical cancer, osteosarcoma, adrenocortical cancer and breast cancer (21,(36)(37)(38)(39)(40). Zhao et al (38) found that miR-195 has a higher sensitivity for breast cancer detection, and the expression level of miR-195 has been found to significantly predict the survival rates of patients with HER2-positive breast cancer (36). Zhang et al (37) reported that use of a serum miRNA panel, comprising miR-16-2*, miR-195, miR-2861 and miR-497, was able to distinguish cervical cancer from cervical intraepithelial neoplasia and healthy controls with high accuracy.…”
Section: Discussionmentioning
confidence: 99%